2014
DOI: 10.1620/tjem.233.129
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B Virus Infection in Patients with Rheumatic Diseases in Tohoku Area: A Retrospective Multicenter Survey

Abstract: Hepatitis B virus (HBV) reactivation has been increasingly recognized in patients receiving chemotherapy and immunosuppressive therapy; however, the prevalence of HBV infection and rate of HBV screening in patients with rheumatic diseases remains unclear. In this study, we aimed to assess the prevalence of HBV infection and fulminant HBV hepatitis in patients with rheumatic diseases. We also investigated the rate of HBV screening before immunosuppressive therapy in patients with rheumatic diseases. A retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
2
28
0
1
Order By: Relevance
“…22 However, most studies that examined the association between HBV infection and RA have been limited to a few HBV cases and specific populations; 7,[12][13][14][15][16]23 whether RA has a pathogenic association with HBV infection remains undetermined. 17 This study involved using a nationwide database from Taiwan, an HBV-endemic country, to examine the association of HBV with RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 However, most studies that examined the association between HBV infection and RA have been limited to a few HBV cases and specific populations; 7,[12][13][14][15][16]23 whether RA has a pathogenic association with HBV infection remains undetermined. 17 This study involved using a nationwide database from Taiwan, an HBV-endemic country, to examine the association of HBV with RA.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Although RA patients receiving biologic agents for immunomodulatory treatment have been associated with the reactivation of HBV infection 10 that may result in liver failure and death, 11 the association of HBV infection and RA remains largely unknown. A few studies have investigated the prevalence of HBV infection in RA patients; most of the these studies have been limited to small sample sizes and specific populations, 7,[12][13][14][15][16] focused on patients who received biologic agents, 11 and could not attain conclusive results. 17 Whether RA has a pathogenic association with HBV infection remains unanswered.…”
mentioning
confidence: 99%
“…The prevalence of concurrent chronic hepatitis B infection in a cohort of RA patients in China was 11.2%, consistent with the prevalence in the general population [13] , although the reported rate of HBsAg in ankylosing spondylitis (AS) by Zheng et al [14] was 25.4%, higher than in the general population or patients with other spondyloarthropathies and RA. In Japan, where approximately 20% Japanese individuals are infected with HBV, HBsAg and HBcAb positive occurred in 0.7% and 25.6% of patients with RA [15] .…”
Section: Diseasesmentioning
confidence: 99%
“…Finally, Cassano et al [48] analyzed 62 psoriatic patients with occult viral infection, treated with anti TNFs agents. There were no signs of HBV activation after a period of 4 years, which supports the safety of the use of immunosuppressant drugs (others than [9] IBD Spain 2009 2056 UC 8% CD 7.1% UC 0.8% CD 0.6% Chevaux et al [10] IBD France 2010 315 UC 1.6% CD 2.8% UC 1.59% CD 0.79% Huang et al [3] IBD China 2014 714 UC 41.6% CD 39.8% UC 5.7% CD 5.3% Kim et al [11] IBD South Korea 2014 513 UC 4.1% CD 3.3% Zou et al [13] RA China 2013 223 11.2% Watanabe et al [15] RA Japan 2014 7650 25.6% 0.7% Conway et al [12] RA Ireland 2014 200 2% 0% Zheng et al [14] AS China 2011 439 25.4% Cohen et al [16] Psoriasis Another prospective study, carried in 41 Chinese adults with idiopatic nephrotic syndrome and inactive hepatitis B, compared standard doses of prednisone vs lower doses of prednisone plus mycophenolate mofetil (MMF) [61] . Without pre-emptive therapy, the risk of exacerbation was lower in MMFprednisone regimen than the group with prednisone in monotherapy, reflecting the major effect of higher doses on the viral reactivation.…”
Section: Hbv Reactivations In Patients With Inflammatory Diseasesmentioning
confidence: 99%
“…Therefore, the prevalence of HBV infection in lupus patients was comparable to that in healthy individuals. In the case of rheumatoid arthritis (RA), the prevalence of resolved HBV infection was reported to be 31.5% (135/428), 25.1% (60/239), and 25.2% (177/703) in Japan (Mori 2011;Urata et al 2011;Watanabe et al 2014). These reports suggested that the rate of HBV infection in lupus patients was lower than in RA patients.…”
Section: Prevalence Of Hbv Infection In Lupus Patientsmentioning
confidence: 99%